Explaining the Role of Head Teachers in the Implementation Quality of Elementary School Educational Program: A Qualitative Study - reza masouminejad (Allameh Tabataba'i University Press, 2019)
The purpose of this study was to investigate the role of head teachers in the process of implementing primary school educational programs. The research approach was qualitative with content analysis method. For this purpose, using purposive sampling, 13 teachers from the north of West Azerbaijan province in the academic year of 1398-99 were selected and semi-structured interviews were conducted until complete data saturation. In order to ensure and validate the accuracy of the data, the method of self-review and receiving feedback from respondents was used. In data analysis, a combined three-step process consisting of King and Harrock (2010), Brown and Clark (2006) and Atrid-Sterling (2001) methods was used. The findings showed that in the themes network, the concept of education strategist is an inclusive theme that describes the position of head teachers with 5 organizing themes(teacher knowledge management, core Assistants, teaching research, professionalism and programming) and 30 basic themes Explains.